1998
DOI: 10.1111/j.1348-0421.1998.tb01969.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Coxiella burnetii from Dust in a Barn Housing Dairy Cattle

Abstract: We attempted to detect Coxiella burnetii in dust samples collected from a barn housing dairy cattle by the polymerase chain reaction (PCR) method. Ten dust samples (five from ventilation fans and five from crossbeams) were collected from two areas in a barn on a farm near Sapporo, Hokkaido. C. burnetii was detected in 5 of the 10 dust samples. It was believed that aerial contamination by C. burnetii occurred in the barn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 14 publications
1
15
0
1
Order By: Relevance
“…The main route of C. burnetii infection is by inhalation of contaminated aerosols containing the microorganism shed from infected animals [1,25,26,28,30,31,34,35]. After becoming infected, female animals shed large quantities of Coxiella into the 424 N. Arricau Bouvery et al environment during abortion or normal delivery through birth fluids, placenta and fetal membranes [3,6,23,24,32].…”
Section: Introductionmentioning
confidence: 99%
“…The main route of C. burnetii infection is by inhalation of contaminated aerosols containing the microorganism shed from infected animals [1,25,26,28,30,31,34,35]. After becoming infected, female animals shed large quantities of Coxiella into the 424 N. Arricau Bouvery et al environment during abortion or normal delivery through birth fluids, placenta and fetal membranes [3,6,23,24,32].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, knowledge of C. burnetii's sources and shedding dynamics is essential to assessing the risks of disease transmission and pathogen persistence. On livestock farms, C. burnetii DNA has been found in various environmental matrices, such as dust (11)(12)(13) and aerosols (14)(15)(16). However, studies that examine the relationship between environmental contamination levels and the clinical status and shedding dynamics of ruminant herds are lacking.…”
mentioning
confidence: 99%
“…Seven studies were not related to a human Q fever outbreak, four of which were performed in areas with a (suspected) high incidence among animals (4,5,21,25). The three other studies reported the presence of C. burnetii DNA in dust (17) or primarily soil samples from a geographically large area in the United States (11,14).…”
mentioning
confidence: 99%